Gezielte Hilfe in schwieriger Zeit? Die Gründung von Schiffshypothekenbanken am Ende des Ersten Weltkriegs - Harald Wixforth (IBF - Institut für Bank- und Finanzgeschichte, 2019)
– The history of German ship mortgage and ship Pfandbrief banks goes back to the end of the First World War. However, the financial crisis from 2007 to 2009 and even more so the current crisis in shipping prevented their business model from coming under increasing criticism. Firstly, this article aims to identify the founding of ship mortgage banks and the motives behind them. Secondly, it is shown that the principle of providing shipping companies with capital against the pledging of shipping space and refinancing itself by issuing Pfandbriefe on the capital market worked well in Germany for almost 100 years. What is more, the ship mortgage banks were and are part of an extraordinarily efficient financial market in Germany, despite all the distortions in the international financial world in recent years.
Keywords: G21; G32; L64; N24; N44; 330